Análise do contexto de trabalho dos dentistas da estratégia saúde da família com relação à prevenção das Iras e Sars-Cov-2, no município de Fortaleza - Melo, Elizabete Araújo (2023)
Dentistry is one of the areas of greatest risk of transmission of the COVID-19 disease, having increased the number of new protocols, guidelines and care that professionals in this area Family Health Strategy, in relation to healthcare-associated infections (HIAS) and SARS-CoV-2. This is a descriptive, cross-sectional, quantitative study, with a simple random sample of 103 dentists from the Primary Care Units (UAPS) in the city of Fortaleza. Data collection took place between June and August 2022, with an online questionnaire sent to the participants’ WhatsApp messaging application. The collected data were he automatically saved by the Google Docs forms resource in a Microsoft Excel spreadsheet and submitted to statistical analysis, using the Statistical Package for the Social Sciences software (SPSS v.19.0). As a result, it was observed that 76,7% of the participants were female; 61,2% in the age group of 36 to 45 years; 96,1% statutory municipal civil servants; 53,3% were satisfied with their work; 70,9% did not belong to any risk group for COVID-19; 63,1% had already tested positive; 100% received at last two doses of the vaccine against COVID-19. It was also observed that the personal protective equipment (PPE) used most frequently by the participants are procedure gloves (99%), which are also the PPE always available in sufficient quantity for the functioning of the dental service; 39,8% the face shield provided by the UAPS has very poor quality, being also the most purchased by the participants; 66% of the UAPS have protocols and standard operating procedures (SOP) for the processing of health products (PPPS); 6,8% have na Internal Accident Prevenction Commission (CIPA); 47,6% have a Health Services Waste Manangement Plan (PGRS); 43,7% have a record of work-related accdents and illnesses; only 1% have a negative pressure respiratory isolation area a High Efficiency Particulate Arrestance (HEPA) filter. It is concluded that, the non-full use of PPE by dentists, the amount available, not always sufficient, by managers, and its questionable quality, added to deficiencies in infrastructure, procedures and biosafety protocols, increase the risk of spreading Iras and Sars-CoV-2 in dental care.